2016
DOI: 10.1021/acs.jmedchem.6b00400
|View full text |Cite
|
Sign up to set email alerts
|

Isatin Derived Spirocyclic Analogues with α-Methylene-γ-butyrolactone as Anticancer Agents: A Structure–Activity Relationship Study

Abstract: Design, synthesis, and evaluation of α-methylene-γ-butyrolactone analogues and their evaluation as anticancer agents is described. SAR identified a spirocyclic analogue 19 that inhibited TNFα-induced NF-κB activity, cancer cell growth and tumor growth in an ovarian cancer model. A second iteration of synthesis and screening identified 29 which inhibited cancer cell growth with low-μM potency. Our data suggest that an isatin-derived spirocyclic α-methylene-γ-butyrolactone is a suitable core for optimization to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(47 citation statements)
references
References 47 publications
0
45
0
Order By: Relevance
“…Other than our previously reported research, a number of other research groups has also proven that the α, β-unsaturated ketone functionality, a Michael acceptor is critical for the cancer cell growth inhibition (Rana et al, 2016;Heller et al, 2015). These examples and our previous research exhibited that uniting an α, β-unsaturated ketone in a new synthetic compound can increase the anticancer attributes of a natural product derivatives, and α, the β-unsaturated moiety can be observed as functionality structure to new drug design.…”
Section: Introductionmentioning
confidence: 63%
“…Other than our previously reported research, a number of other research groups has also proven that the α, β-unsaturated ketone functionality, a Michael acceptor is critical for the cancer cell growth inhibition (Rana et al, 2016;Heller et al, 2015). These examples and our previous research exhibited that uniting an α, β-unsaturated ketone in a new synthetic compound can increase the anticancer attributes of a natural product derivatives, and α, the β-unsaturated moiety can be observed as functionality structure to new drug design.…”
Section: Introductionmentioning
confidence: 63%
“…18, 34 Nonetheless, the non-disulfide, nucleophilic cysteines, Cys38 and Cys120, located at the p65 DNA-binding interface constitute unique structural features of p65 that lends itself towards the development of covalent chemical modulators. Furthermore, previous studies from other groups have demonstrated covalent engagement of p65 Cys38 with diverse small molecules, 6, 3741 as well as covalent targeting of p65 Cys120. 42 …”
Section: Introductionmentioning
confidence: 85%
“…Recently, by means of molecular docking followed by in cellulo screening we uncovered that Isatin Schiff and Mannich based derivatives (ISMBDs) were able to activate p53 [42]. In line with this, Rana and colleagues have shown that isatin-derived spirocyclic a-methylene-g-butyrolactone can be used as a novel anticancer agent [43]. Furthermore, a series of isatin-based heterocyclic compounds were found to inhibit proliferation of cancer cell lines resistant to apoptosis [44].…”
Section: Introductionmentioning
confidence: 93%